2017
DOI: 10.1007/s41095-017-0082-8
|View full text |Cite
|
Sign up to set email alerts
|

Joint head pose and facial landmark regression from depth images

Abstract: This paper presents a joint head pose and facial landmark regression method with input from depth images for realtime application. Our main contributions are: firstly, a joint optimization method to estimate head pose and facial landmarks, i.e., the pose regression result provides supervised initialization for cascaded facial landmark regression, while the regression result for the facial landmarks can also help to further refine the head pose at each stage. Secondly, we classify the head pose space into 9 sub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 38 publications
0
6
0
Order By: Relevance
“…In separate work, [34] used a similar approach by proposing an application of cascaded random forest on nine sub-space classifications of the head pose with each specific space trained by a global shape constraint. This classificationbased method efficiently handled the problem of significant pose variations.…”
Section: B Facial Feature Recommendationsmentioning
confidence: 99%
See 1 more Smart Citation
“…In separate work, [34] used a similar approach by proposing an application of cascaded random forest on nine sub-space classifications of the head pose with each specific space trained by a global shape constraint. This classificationbased method efficiently handled the problem of significant pose variations.…”
Section: B Facial Feature Recommendationsmentioning
confidence: 99%
“…With the strong computational ability and robust design feature, the deep learning model keeps the features with maximum weight and contribution and discards the rest. It gives results based on a series of non-linear operations [34].…”
Section: B Datasetsmentioning
confidence: 99%
“…For example, the head pose of a user may indicate that the user is not looking at the screen. Research in this domain has shown that head pose and facial landmarks, such as eye corners, nose tip, mouth, and chin, can accurately be detected and that this detection is important for face detection and recognizing facial expressions [37]. Facial expressions of users might reveal their feelings about the content or their experience of using the service.…”
Section: Related Workmentioning
confidence: 99%
“…In recent years, research related to "humans" in the computer vision community has become increasingly active because of the high demand for real-life applications. There has been much good research in the fields of human pose estimation [1,2,6,14,20,26,40], pedestrian detection [25,41,42], portrait segmentation [35,36,37], and face recognition [18,23,24,27,39,43,44], much of which has already produced practical value in real life. This paper focuses on multi-person pose estimation and human instance segmentation, and proposes a pose-based human instance segmentation framework.…”
Section: Introductionmentioning
confidence: 99%